ISOLASI DAN UJI ANTAGONIS BAKTERI ASAL TANDAN KOSONG SAWIT YANG DIAPLIKASIKAN PADA AREAL TANAMAN KARET TERHADAP PENYAKIT JAMUR AKAR PUTIH (R. microporus) - Priyo Adi Nugroho; Cici Indriani Dalimunthe (Jurnal Agro Estate, 2020)
The concern of oil palm empty fruit bunches (OPEFB) utilization in the rubber field that potential to be a host of white root disease needs to be deeply investigated. The objective of this study was to assess the bacteria on the surface of OPEFB that able to inhibit the growth of R. microporus fungi. The antagonistic assay of eight isolates of bacteria against R. microporus fungi was conducted in the Plant Protection Laboratory of Sungei Putih Research Centre. The isolates were isolated from the surface of OPEFB applied in the rubber field. Nutrient agar (NA) was employed in the isolation and purification of bacteria. The antagonistic assay was carried out in vitro using the dual culture method. The observation was performed on 2, 4, 6, and 8 days after incubation (DAI). The result indicated that the eight isolates have varied in inhibition ability of R. Microporus fungi. The initial inhibition was started since 2 DAI particularly in the isolates B2, B3, B4, and B7. The percentage of inhibition were 30%, 60%, 65% dan 69% respectively. Until 8 HSI, the isolates B2, B3, B4, B6, B7, and B8 were still inhibiting the growth of R. microporus fungi > 80%. The isolates B3 and B4 showed the best performance in fungi inhibition with the percentage > 95%. Whereas, the ability of inhibition of the isolates B1 and B5 were very low as < 50%. The existence of such antagonistic bacteria perhaps led to OPEB was not role as the host of white root disease while applied in the rubber field